Application of response surface methodology to tailor the surface chemistry of electrospun chitosan-poly(ethylene oxide) fibers. (15th April 2018) - Bösiger, Peter; Richard, Isabelle M.T.; Le Gat, Luce; Michen, Benjamin; Schubert, Mark; Rossi, René M.; Fortunato, Giuseppino
Highlights: Development of electrospun chitosan/PEO blend fibers with tailored surface properties. Designing of a response surface model (RSM) exhibiting excellent prediction accuracy. Chitosan fibers exhibiting tailored nitrogen atomic surface content of up to 6.4%. Nitrogen surface content is significantly determined by chitosan Mw and polymers mixing ratio. Nitrogen surface content strongly influences the membranes zeta potential. Abstract: Chitosan is a promising biocompatible polymer for regenerative engineering applications, but its processing remains challenging due to limited solubility and rigid crystalline structure. This work represents the development of electrospun chitosan/poly(ethylene oxide) blend nanofibrous membranes by means of a numerical analysis in order to identify and tailor the main influencing parameters with respect to accessible surface nitrogen functionalities which are of importance for the biological activity as well as for further functionalization. Depending on the solution composition, both gradient fibers and homogenous blended fiber structures could be obtained with surface nitrogen concentrations varying between 0 and 6.4%. Response surface methodology (RSM) revealed chitosan/poly(ethylene oxide) ratio and chitosan molecular weight as the main influencing factors with respect to accessible nitrogen surface atoms and respective concentrations. The model showed good adequacy hence providing a tool to tailor the surface properties of chitosan/poly(ethylene oxide) blends by addressing the amount of accessible chitosan.